PERCEPTION OF WAR AMONG THE PEOPLES OF DAGESTAN - Kurbanov, H T (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the problem of understanding the war, covers internal content and meaning of conduct of the wars, in which Dagestan people took part. The author presents war typology, makes an attempt to understand and associate political culture with military theme. It is noted that the war in Dagestan is a symbol code for inoculation of patriotism and civic identity.
Keywords: war; jihad; political culture; the Arabs; geopolitics; Islam